Exchange and Market Relations - Stoilova, Vyara (Research Papers, 2010)
The study ‘Exchange and Market Relations’ examines the transformation of the whole variety of relations of exchange among people into market relations and the gradual establishment of market relations in the society. The process of establishment of market relations is considered from the point of view of its economic prerequisites and ‘the establishment of market relations’ is represented as dominance of economic thought and as a kind of ‘play of growth’ of benefits sought by the actor.Special attention is dedicated to the consequences resulting from the establishment of market relations over the life of the individual, such as alienation, identity problems, attitude towards wealth, and subjective perception of happiness and contentment.